Aquatic macroinvertebrate diversity in mosquito larval habitats in São Tomé and Príncipe - Maria Júlia Maciel Corrêa; Madizalda Ceita; Robert E. Ditter; Melina Campos; Hester Weaving; Andrew Goffinet; Claire M. Egan; João Viegas; Anthony J. Cornel; Gregory C. Lanzaro; João Pinto (PLoS ONE, 2026)
Oceanic islands harbor unique aquatic ecosystems characterized by distinct macroinvertebrate communities that play vital roles in ecosystem functioning and stability. São Tomé and Príncipe islands (STP), located in the Gulf of Guinea, represent a model system where the primary malaria vector, Anopheles coluzzii , shares larval habitats with a diversity of aquatic taxa. Here, we evaluate macroinvertebrate diversity in permanent and temporary larval habitats typical of An. coluzzii in STP during the wet and dry seasons. We collected 5,208 macroinvertebrates belonging to eight classes, 15 orders, and 51 families. These included insects, crustaceans, spiders, annelid worms, springtails, and mollusks, with insects and crustaceans dominating collections. Diversity remained stable across the wet and dry seasons, but higher diversity was found in permanent habitats when compared to temporary habitats. We found 9 families (12% relative abundance) that included potential predators of mosquito vector larvae. Our results demonstrate that larval habitats of An. coluzzii support a dynamic community of aquatic macroinvertebrates. Establishing this ecological baseline is crucial for future assessments of community composition and for informing sustainable vector control management and biodiversity conservation on these islands.